2018
DOI: 10.5455/umj.20180117091224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan Fasting on the International Normalized Ratio in Patients with Mechanical Prosthetic Heart Valves

Abstract: Around the world, a Muslim population of more than 1.6 billion perform an obligatory religous act of Fasting (Siyam) during the Holy month of Ramadan, which correspond to the 9 th month of the Hijra Calendar (1). Religious fasting includes abstenance from food and drink from dawn to dusk (2). During Ramadan a lot of Muslim societies undergo significant lifestyle modifications, including dietary pattern. These dietary modifications, along with the prolonged day-time fasting and medication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Alghamdi et al [69] evaluated the effect of RF on the international normalized ratio (INR) stability in patients using warfarin anticoagulation for mechanical prosthetic heart valves. Data were extracted retrospectively from a specialized anticoagulation clinic electronic database and were analyzed in a case-control manner, where Ramadan INR of each study subject was compared to his/her own pre-Ramadan INR level.…”
Section: Vascular Disease and Risk Factorsmentioning
confidence: 99%
“…Alghamdi et al [69] evaluated the effect of RF on the international normalized ratio (INR) stability in patients using warfarin anticoagulation for mechanical prosthetic heart valves. Data were extracted retrospectively from a specialized anticoagulation clinic electronic database and were analyzed in a case-control manner, where Ramadan INR of each study subject was compared to his/her own pre-Ramadan INR level.…”
Section: Vascular Disease and Risk Factorsmentioning
confidence: 99%
“…However, a study of Awiwi et al, (9), while contradicting our results regarding INR changes during Ramadan, noticed fluctuations in the quality of anticoagulation throughout their study, with the largest fluctuation in the ratio of patients with optimal therapeutic anticoagulation observed between Ramadan and the first week post-Ramadan (87.5% vs. 60.0%). On the other hand, a study concluded that mean INR insignificantly decreased during Ramadan compared to pre-Ramadan, despite fluctuations in INR results during Ramadan, with 66% of patients within the desired therapeutic range during Ramadan, down from 74% pre-Ramadan (12). During Ramadan, there was an increase in out-of-range INR values, particularly in the supra-therapeutic direction, affecting both high and low target INR groups.…”
Section: Discussionmentioning
confidence: 97%
“…Alghamdi et al 2018 published a retrospective study on the effect of Ramadan fasting on the INR level in Saudi patients using warfarin for prosthetic heart valve anticoagulation 4 . They found no difference in the INR at baseline (pre‐Ramadan) compared to Ramadan.…”
Section: Discussionmentioning
confidence: 99%
“…During Ramadan, most adult Muslims abstain from eating and drinking from dawn to sunset, which is considered short-term fasting [1][2][3] and called "Siyam." 4 Although fasting is not obligatory for individuals with health issues, a majority of patients, including those with thrombotic diseases, choose to fast during Ramadan to observe the spirituality of this month. Food abstinence applies to everything reaching the stomach, including oral medications such as warfarin.…”
Section: Introductionmentioning
confidence: 99%